Quran Teachers’ Skills as Pedagogical Foundations: Conceptual and Practical Insights into Nine Competencies - Engkizar Engkizar; Azhar Jaafar; Mohd Isa Hamzah; Syafrimen Syafril; Afifah Febriani; Gifa Oktavia; Ardi Satrial (International Islamic Studies Development and Research Center (IISDRC), 2026)
The teaching of the Quran requires teachers to master fundamental instructional skills comprehensively, as they are not merely transmitters of sacred texts but also facilitators of effective, interactive, and meaningful learning processes. Such mastery enables teachers to foster students’ motivation, improve the quality of recitation, and cultivate an emotional connection with the Quran. This study aims to examine the concept and practice of nine essential teaching skills in Quranic instruction and to explore how these skills are implemented in classroom settings. Employing a qualitative content analysis approach, data were drawn from theories, expert opinions, and the review of 120 relevant scholarly articles. Thematic analysis was conducted using NVivo 12 software. The findings highlight nine core teaching skills that Quran teachers must acquire both theoretically and practically: i) openings and ii) closures enhance attentiveness and reflection, iii) explanation and iv) questioning strengthen comprehension and critical engagement, v) reinforcement and vi) variation sustain motivation, while vii) classroom management, viii) group discussions, ix) and individualized teaching foster discipline, collaboration, and inclusivity. This study contributes theoretically by strengthening the conceptual framework of basic teaching skills within Islamic education, and practically by offering insights for teacher training, curriculum development, and policy initiatives aimed at enhancing the quality of Quranic pedagogy in Islamic educational institutions.